Drug Use Patterns In Stroke Patients Ichemic Inpatience In RSUD dr. Soegiri Lamongan - Sari, Kumala (LP2M IIK (Lembaga Penelitian dan Pengabdian Masyarakat Institut Ilmu Kesehatan) Bhakti Wiy, 2024)
Stroke or Cerebrovascular accident is a clinical symptom that develops rapidly as a result of focal or global brain function disturbance due to blockage or rupture of brain blood vessels, with symptoms lasting more than 24 hours. Stroke is the sudden death of several brain cells due to lack of oxygen due to blockage or rupture of a cerebral artery that blocks blood flow to the brain. This study aims to determine the pattern of drug use in inpatient ischemic stroke patients at RSUD dr. Soegiri Lamongan. Non-experimental research method with a descriptive research design in the form of retrospective collection of medical record data. The samples taken in this study were 86 medical record data of patients who met the inclusion criteria. The results showed that the highnest pattern of drug use in ischemic stroke patients used a combination of 2 drugs use that was the neuroprotectant-antiplatelet in 42 patients (48,8%), the combination of 3 drugs use that was the neuroprotectant-antiplatelet-antihypertension in 13 patient (15%), and a combination of 4 combination drug use that was the neuroprotectant-antiplatelet-antihypertension-antidislipidemia in 8 patient (9,3%). The most widely used neuroprotectant group was citicolin in 77 patients (79,38%), the antiplatelet clopidogrel in 67 patients (50,76%) and aspilet in 65 patients (49,24%), the antihypertension amlodipine in 19 patients (31,67%) and candesartan in 17 patients (28,33%), and the antidyslipidemia atorvastatin in 9 patients (64,29%)